Temporal discrimination, a cervical dystonia endophenotype: Penetrance and functional correlates. - WALSH, CATHAL; REILLY, RICHARD (My University, 2014)
The pathogenesis of adult-onset primary dystonia remains poorly understood. There is variable age-related and gender-related expression of the phenotype, the commonest of which is cervical dystonia. Endophenotypes may provide insight into underlying genetic and pathophysiological mechanisms of dystonia. The temporal discrimination threshold (TDT)-the shortest time interval at which two separate stimuli can be detected as being asynchronous-is abnormal both in patients with cervical dystonia and in their unaffected first-degree relatives. Functional magnetic resonance imaging (fMRI) studies have shown that putaminal activation positively correlates with the ease of temporal discrimination between two stimuli in healthy individuals. We hypothesized that abnormal temporal discrimination would exhibit similar age-related and gender-related penetrance as cervical dystonia and that unaffected relatives with an abnormal TDT would have reduced putaminal activation during a temporal discrimination task. TDTs were examined in a group of 192 healthy controls and in 158 unaffected first-degree relatives of 84 patients with cervical dystonia. In 24 unaffected first-degree relatives, fMRI scanning was performed during a temporal discrimination task. The prevalence of abnormal TDTs in unaffected female relatives reached 50% after age 48 years; whereas, in male relatives, penetrance of the endophenotype was reduced. By fMRI, relatives who had abnormal TDTs, compared with relatives who had normal TDTs, had significantly less activation in the putamina and in the middle frontal and precentral gyri. Only the degree of reduction of putaminal activity correlated significantly with worsening of temporal discrimination. These findings further support abnormal temporal discrimination as an endophenotype of cervical dystonia involving disordered basal ganglia circuits.
PUBLISHED
Keywords: cervical dystonia; Neuroscience; Next Generation Medical Devices